2020
DOI: 10.2147/hiv.s233786
|View full text |Cite
|
Sign up to set email alerts
|

<p>Determinants of Male Partner Involvement Towards Prevention of Mother to Child Transmission Service Utilization Among Pregnant Women Who Attended Focused Antenatal Care in Southern Ethiopia</p>

Abstract: Background: Male partner involvement is an important and crucial determinant of prevention of mother to child transmission (PMTCT) of HIV. It creates an opportunity to reverse the transmission of HIV during pregnancy, labor, and breastfeeding. Thus, involving male partners during HIV screening of pregnant mothers at ANC is the key to fight against MTCT of HIV. Objective: This study was designed to assess the magnitude and factors associated with male partner's involvement on PMTCT service utilization among pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
2
2
Order By: Relevance
“…Constant engagement of men has been reported to have positive effects on men’s participation and their involvement particularly being related to improved knowledge of PMTCT and higher engagement in HIV and pregnancy-safe practices ( Melis & Fikadu, 2022 ; OPHID, 2015 ). However, contrasting with other studies ( Ayalew et al, 2020 ), less than 50% of the men in our study were returning clients with the rest presenting for the first time. Our findings indicate that there is a gap between attracting men to the ANC program and keeping them engaged in the program.…”
Section: Discussioncontrasting
confidence: 99%
“…Constant engagement of men has been reported to have positive effects on men’s participation and their involvement particularly being related to improved knowledge of PMTCT and higher engagement in HIV and pregnancy-safe practices ( Melis & Fikadu, 2022 ; OPHID, 2015 ). However, contrasting with other studies ( Ayalew et al, 2020 ), less than 50% of the men in our study were returning clients with the rest presenting for the first time. Our findings indicate that there is a gap between attracting men to the ANC program and keeping them engaged in the program.…”
Section: Discussioncontrasting
confidence: 99%
“…It could also be that these had couple’s HIV testing which increases HIV testing for pregnant women, a component of the PMTCT cascade [ 41 ]. Our results are consistent with those of a study in Ethiopia in 2015 whereby the odds of utilizing PMTCT services among mothers whose partners had undergone HIV counseling and testing were 8.2 times those of mothers whose partners had not undergone it [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with previous studies in western Kenya, Uganda and Tanzania where the proportion of male involvement was 55.8%, 77.8% and 54.4%, respectively [ 20 , 24 , 35 ]. However, this study reported almost double the levels of male involvement that have been documented in other studies in Nairobi, Kenya (26.2%), Ethiopia (29.8%), and Ghana (35%) [ 21 , 23 , 36 ].…”
Section: Discussioncontrasting
confidence: 49%
“…Unfortunately, over the years, male partner involvement in antenatal care has been wanting globally and more so in low and middle income countries. In particular, countries in SSA that account for the larger share of maternal deaths have reported correspondingly low levels of male involvement which include 54% in Tanzania [ 20 ], 29.8% in Ethiopia [ 21 ], 6% in Wakiso District, Uganda [ 22 ] and 26% in Nairobi, Kenya [ 23 ].…”
Section: Introductionmentioning
confidence: 99%